Tourmaline chemistry in the metamorphic rocks of the central Nepal Himalaya - Rai, Santa Man; Fort, Patrick Le (Journal of Nepal Geological Society, 2002)
Tourmaline occurs in various tectonic units of the Himalaya. It is found in almost all formations, from the Lesser Himalaya to the Tibetan-Tethys Sedimentary Series. They are also found in the Cambro-Ordovician granite of the Kathmandu nappe and Miocene leucogranites of the Higher Himalaya. The chemical composition of tourmalines from the central Nepal Himalaya is presented in schorlite (Fe)-dravite (Mg) elbaite (Al) diagram. The variation in chemistry of tourmaline in different types of rock is found to depend on the composition of the host rocks, the grade of metamorphism and the position in the structural edifice. The chemical results show that the Mg-rich tourmaline (dravite) is found to be concentrated in marble, calcic gneiss, whereas schorlite elbaite end members are found in the pelitic gneiss, mica schist, migmatitc, and quartzite, with little increase of elbaite content. The Lesser Himalayan tourmalines show a correlation between their chemistry and the grade of metamorphism of the host rocks. The Mg content of the tourmaline increases whereas Fe and Al contents decrease from chlorite to kyanite isograd. In the chlorite isograd rocks, the tourmalines are detritic in origin and are affected very little by the low-grade metamorphism. With increasing grade of metamorphism, the fluids rich in boron are mobilized in the schist and quartzite, and reacted with aluminium silicate associated elements resulting in the crystallization of the tourmalines. In the Higher Himalayan Crystallines, where the temperature remains constant and the pressures decreases upward in the hanging wall of the MCT, the composition of the tourmaline is found to be evolved with an increase of Fe content and decrease of Mg and Al contents in the higher structural level.